2023
DOI: 10.1111/phpp.12855
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vascular patterns during the treatment of psoriatic patients using narrow‐band ultraviolet B phototherapy by the dermoscope

Abstract: Background Phototherapy is a traditional treatment for psoriasis and patients using it for a long time may be exposed to cumulative toxicity, so dermatologists need continuously diagnostic tools that help in monitoring the disease progression. Objectives To detect dermoscopic changes with the improvement of skin in patients with chronic plaque psoriasis on narrow‐band ultraviolet B phototherapy and evaluate the role of dermoscopy in monitoring the patients. Methods Narrowband ultraviolet B phototherapy was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Dermoscopy can provide detailed visualization of key dermatoscopic features, allowing for the identification of subtle changes, and provides a more accurate evaluation of the treatment response (13). Changes in the vessel patterns were reported to be a predictor of the response of psoriatic patients to phototherapy (14). In both treatment sides, we observed similar vascular changes, implying a comparable mechanism of action for both types of light.…”
Section: Discussionsupporting
confidence: 74%
“…Dermoscopy can provide detailed visualization of key dermatoscopic features, allowing for the identification of subtle changes, and provides a more accurate evaluation of the treatment response (13). Changes in the vessel patterns were reported to be a predictor of the response of psoriatic patients to phototherapy (14). In both treatment sides, we observed similar vascular changes, implying a comparable mechanism of action for both types of light.…”
Section: Discussionsupporting
confidence: 74%
“…In recent years, several studies have shown that there is a correlation between the treatment outcome of psoriasis and the specific dermoscopic features, such as the hemorrhagic dots and blood vessel diameter, which makes dermoscopic features a potential predictor of the curative effect on psoriasis 74,78,79 …”
Section: Prediction and Monitoringmentioning
confidence: 99%
“…The two look similar under handheld dermoscopy, 81 thus earlier studies did not consider the classification of dotted vessels by diameter to be of diagnostic significance 82 . However, recent studies have shown that the globular vessels are associated with treatment resistance, while the dotted vessels predict better treatment outcomes in local treatments, such as calcipotriene plus betamethasone dipropionate aerosol foam, narrowband ultraviolet B phototherapy, and 650‐microsecond 1064‐nm Nd:YAG laser 70,78,79 . Several studies have found that globular vessels are more likely to be observed in the legs, where the dotted vessels appear less frequently than in other parts of the body 12,70,79 .…”
Section: Prediction and Monitoringmentioning
confidence: 99%
See 2 more Smart Citations